Transplantation and inflammation: implications for the modification of chemokine function. Issue 2 (October 2014) - Barker, Catriona E.; Ali, Simi; O'Boyle, Graeme; Kirby, John A.
Summary Oxidative stress is a major and recurring cause of damage during inflammation, especially following organ transplantation. Initial ischaemia–reperfusion injury causes the production of many reactive oxygen and nitrogen species, and subsequent recruitment and activation of inflammatory cells can lead to further oxidative stress. This stress is well known to cause damage at the cellular level, for example by induction of senescence leading to the production of a characteristic senescence‐associated secretory phenotype. Chemokines are an important component of the senescence‐associated secretory phenotype, recruiting further leucocytes and reinforcing the stress and senescence responses. As well as inducing the production of proteins, including chemokines, oxidative stress can alter proteins themselves, both directly and by induction of enzymes capable of modification. These alterations can lead to important modifications to their biological activity and also alter detection by some antibodies, potentially limiting the biological relevance of some immunochemical and proteomic biomarkers. Peroxynitrite, a reactive nitrogen species generated during inflammation and ischaemia, can cause such modifications by nitrating chemokines. Matrix metalloproteinases, released by many stressed cells, can cleave chemokines, altering function, while peptidylarginine deiminases can inactivate certain chemokines by citrullination. This review discusses the relationship between inflammation and post‐translational modification, focusing on the functional modulation of transplant‐relevant pro‐inflammatory chemokines.